High-Throughput Task to Study Memory Recall During Spatial Navigation in Rodents - Morales, Lucia; Tomàs, David P.; Dalmau, Josep; de la Rocha, Jaime; Jercog, Pablo E. (Frontiers in Behavioral Neuroscience, 2020)
Spatial navigation is one of the most frequently used behavioral paradigms to study memory formation in rodents. Commonly used tasks to study memory are labor-intensive, preventing the simultaneous testing of multiple animals and tend to yield a low number of trials, curtailing the statistical power. Moreover, they are not tailored to be combined with neurophysiology recordings because they are not based on overt stereotyped behavioral responses that can be precisely timed. Here we present a novel task to study long-term memory formation and recall during spatial navigation. The task consists of learning sessions during which mice need to find the rewarding port that changes from day to day. Hours after learning, there is a recall session during which mice search for the location of the memorized rewarding port. During the recall sessions, the animals repeatedly poke the remembered port over many trials (up to 20) without receiving a reward (i.e. no positive feedback) as a readout of memory. In this task, mice show memory regarding ports learned on up to 3 previous days. This 8-port maze task requires minimal human intervention, allowing for simultaneous and unsupervised testing of several mice in parallel, yielding a high number of recall trials per session over many days, and compatible with recordings of neural activity.